1997
DOI: 10.1111/j.1751-1097.1997.tb03238.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Fluence Rate Effects in Photodynamic Reactions with AIPcS4 as Sensitizer

Abstract: It has been shown previously that the efficiency of photodynamic therapy (PDT) both in vivo and in vitro is dependent on fluence rate. In this study, different in vitro experiments showed that tetrasulfonated aluminum phthalocyanine (AIPcS4) is more efficient in photosensitization if the light is delivered at low fluence rate. Erythrocyte damage, virus inactivation and photooxidation of reduced glutathione (GSH) and histidine were all enhanced if light was delivered at 100 W/m2 as compared to 500 W/m2. Bleachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Of particular importance is the observation that PDT-induced cytotoxicity is critically dependent on both radiant exposure and the rate of light delivery (irradiance)-lower irradiances are more effective, especially at low radiant exposures. The decreased efficacy of higher irradiances observed in BT 4 C monolayers is in good agreement with the findings of other investigators using a variety of cell lines and photosensitizers [25,26]. Oxygen depletion, which has been shown to be important in fluence rate effects observed in vivo, is likely not involved.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Of particular importance is the observation that PDT-induced cytotoxicity is critically dependent on both radiant exposure and the rate of light delivery (irradiance)-lower irradiances are more effective, especially at low radiant exposures. The decreased efficacy of higher irradiances observed in BT 4 C monolayers is in good agreement with the findings of other investigators using a variety of cell lines and photosensitizers [25,26]. Oxygen depletion, which has been shown to be important in fluence rate effects observed in vivo, is likely not involved.…”
Section: Discussionsupporting
confidence: 79%
“…Oxygen depletion, which has been shown to be important in fluence rate effects observed in vivo, is likely not involved. The observed effect may be due to different mechanisms operating under high and low fluence rates, involving oxidizing intermediates [25]. The data presented in Figure 1 give a good estimate of the light delivery conditions required for optimum PDT effect in this cell line, and therefore provide a good starting point for further study in animals.…”
Section: Discussionmentioning
confidence: 87%
“…Similar results were obtained with an electron microscopic and serological analysis of the platelets derived from HpD treated normal mice showed that platelet necrosis proceeds rapidly with almost all platelets were necrotized after 8 h. Even directly after irradiation some platelets exhibited swelling and deformation [68]. Similarly, PDT-related erythrocyte damage has been shown to be light-dependent [69].…”
Section: Photodynamic Platelet-dye Interactionssupporting
confidence: 73%
“…Another in vitro study examining the effect of lower fluence rate excitation, using a phthalocyanine sensitizer, has found that damage was enhanced at lower fluence rates (53). In that work it was also proposed that different mechanisms operate under low and high fluence rates, involving oxidizing intermediates.…”
Section: Discussionmentioning
confidence: 99%